2001
DOI: 10.2355/isijinternational.41.63
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic, Static and Metadynamic Recrystallization of a Nb-microalloyed Steel.

Abstract: Using hot torsion tests, the dynamic (DRX), static (SRX) and metadynamic (MDRX) recrystallization characteristics of a Nb-microalloyed steel were studied. The torsion tests were carried out at temperatures in the range 850 to 1 050°C with strain rates ranging from 0.5 to 5/sec. At the higher temperatures, the Nb remained in solution, while precipitation was underway in the lower temperature range. The results indicate that Nb precipitation has little influence on the value of the critical strain (e c ) for dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 10 publications
5
51
2
4
Order By: Relevance
“…The rate of softening decreased with a decrease in the applied strain due to a lower dislocation density which provides the driving force for SRX (that is a nucleation and growth process). 15) The SRX, in agreement with previous studies 5,15) was observed in all annealing conditions for the alloy used in this work (Figs. 4 and 5).…”
Section: Kinetics Of Recrystallizationsupporting
confidence: 81%
See 1 more Smart Citation
“…The rate of softening decreased with a decrease in the applied strain due to a lower dislocation density which provides the driving force for SRX (that is a nucleation and growth process). 15) The SRX, in agreement with previous studies 5,15) was observed in all annealing conditions for the alloy used in this work (Figs. 4 and 5).…”
Section: Kinetics Of Recrystallizationsupporting
confidence: 81%
“…A number of authors 13,15) have even suggested discontinuities between conventional static and metadynamic recrystallization. This is clear from Fig.…”
Section: Initiation Of Strain Independent Softeningmentioning
confidence: 99%
“…They then become supersaturated when the temperature is lower than the critical temperature because of the difference between the amount of microalloying elements being dissolved after reheating and microalloying elements dissolution limit in equilibrium condition at various temperatures. The degree of supersaturation is the potential for precipitation and it can be described by a factor, supersaturation ratio [35,[89][90][91][92][93][94][95][96]. The supersaturation ratio is calculated by the solubility product of different microalloying elements at different temperatures using the following equation:…”
Section: Solubility Productmentioning
confidence: 99%
“…and after deformation, however, limited studies have been reported on the microstructural evolution in terms of recrystallized volume fraction and grain size. A large group of these models are based on the Johnson-Mehl-Avrami-Kolmogorov (JMAK) equation approach [15][16][17][18][19][20][21]. However, the ideal JMAK behavior is rarely exhibited by real materials.…”
Section: Introductionmentioning
confidence: 99%